Synthesis, spectroscopic characterization and structural investigations of new adduct compound of carbazole with picric acid: DNA binding and antimicrobial studies - Saravanabhavan, Munusamy; Sathya, Krishnan; Puranik, Vedavati G.; Sekar, Marimuthu (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2014)
Carbazole picrate (CP), a new organic compound has been synthesized, characterized by various analytical and spectroscopic technique such as FT-IR, UV-Vis, H-1 and C-13 NMR spectroscopy. An orthorhombic geometry was proposed based on single crystal XRD study. The thermal stability of the crystal was studied by using thermo-gravimetric and differential thermal analyses and found that it was stable up to 170 degrees C. Further, the newly synthesized title compound was tested for its in vitro antibacterial and antifungal activity against various bacterial and fungal species. Also, the compound was tested for its binding activity with Calf thymus (CT) DNA and the results show a considerable interaction between CP and CT-DNA. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial activity and DNA-interaction; CP adduct; Single crystal XRD; TG-DTA